Anxiety and associated factors in Northwest Ethiopian pregnant women: a broad public health concern - Haile, Tsion Tadesse; Kebede, Azmeraw Ambachew; Gessesse, Dereje Nibret; Tsega, Nuhamin Tesfa; Aklil, Mastewal Belayneh; Temesgan, Wubedle Zelalem; Anteneh, Tazeb Alemu; Tibebu, Nebiyu Solomon; Alemu, Haymanot Nigatu; Seyoum, Asmra Tesfahun; Tiguh, Agumas Eskezia; Yismaw, Ayenew Engida; et al. (Frontiers in Public Health, 2024)
Introduction: Pregnancy-related anxiety is a prevalent mental health issue that mostly affects women in low-income nations like Ethiopia. It has been linked to unfavorable pregnancy outcomes, such as miscarriage, prematurity, and low birth weight. However, it has often received less attention and community-based evidence lacks on its prevalence and associated factors. Thus, the purpose of this study was to assess the prevalence and associated factors of Anxiety in Northwest Ethiopian pregnant women in Gondar city.Methods: A community-based cross-sectional study was conducted from July 1 st to August 30 th , 2021 in Gondar city. A cluster sampling technique was used to select a sample of 872 pregnant women and in-person interviews were conducted to gather data. Descriptive and analytical statistical procedures were carried out.Results: Of the participants, pregnancy-related anxiety was reported in 29.4% (95% CI: 26.3, 32.4) of women. The likelihood of having anxiety was higher among women who had known